Supramolecular Polymer Network Membranes with Molecular‐Sieving Nanocavities for Efficient Pre‐Combustion CO2 Capture. Issue 1 (1st December 2021) - Wu, Ji; Chung, Tai‐Shung
Abstract: Pre‐combustion membrane CO2 capture from syngas before utilizing the clean hydrogen fuel, demands very challenging membrane materials with simultaneous high thermal resistance, precise subnanometer size‐selectivity, and robust processability. Here, an unconventional yet ultra‐facile nanocomposite membrane design using 4‐sulfocalix[4]arene (SCA4) molecules, a highly interactive member of soluble organic macrocyclic cavitands (OMCs) with a precise ≈3.0Å open cavity, is reported, to effectively sieve CO2 (3.3Å) from H2 (2.89Å). By simply infiltrating dissolved SCA4 molecules into prefabricated polymer membranes, they form extensive 3D supramolecular polymer networks (SPNs) with the polymer backbones through multi‐site ionic interactions. Bearing distinctly molecular‐sieving nanocavities, these otherwise amorphous SPN membranes deliver drastically enhanced mixed‐gas H2 /CO2 separation under an industrial high‐temperature‐and‐pressure environment with 4.35 times higher selectivity being achieved, allowing them to well outperform most existing polymer‐based materials and even rival many state‐of‐the‐art but delicate inorganic and framework‐based membranes. They also demonstrate enhanced mechanical properties and long‐term operation stability. Most attractively, the SPN membranes obtain a molecularly homogeneous, single‐phase composite structure that can significantly surpass conventional phase‐segregated mixed‐matrix membranes in processability. Accompanied by the widely tunable OMC structures, this work can provide a versatile toolbox for designing advanced molecular‐sieving membranes with an optimal balance of performance, robust properties, and scalability. Abstract : Current large‐scale H2 production requires robust and scalable size‐sieving membrane materials for efficient CO2 capture from syngas. This work innovatively utilizes the supramolecular polymer network structure with precise nanocavities in nanocomposite membrane design. It provides a seamless integration of the versatile processability and robust properties of amorphous polymers with sharp molecular‐sieving abilities of porous nanoarchitectures for superior H2 /CO2 separation.